Professor Langford's Meaning of 'Miracle' - Tan, Tai Wei (Religious studies, 1972)
In his paper The Problem of the Meaning of "Miracle" (Religious Studies, March, 1971), Professor Michael J. Langford proffers a concept of miracles that derives its intelligibility from the familiar phenomenon of the interaction of minds. Miraculous occurrences are portrayed as a variant, though abnormal, form of what we may term inter-psychosomatic influence', God's mind being the ultimate determinant. Langford thinks that to speak significantly of miracles, the phenomenon should be understood as not totally dissimilar to our previous experience' (p. 49); hence the familiar notion of inter-psychosomatic influence. He thinks, too, that to talk of miracles as God interfering directly with the natural order would be to admit that such interference would not upset our concept of human nature and responsibility, a consequence which, to Langford, would make it inconsistent for Christians to maintain the free-will defence in the face of the problem of evil. According to Langford, human interference with the natural order does not vitiate the preconditions of human responsibility, and so he thinks that his concept of miracle, which is only an extension of the same phenomenon, of a kind that also does not disrupt either human freedom or the stable order that is the necessary context for human life' (p. 49), will provide a way out of the dilemma. Having agreed with Hume and Flew that it would be unreasonable to explain an unusual event by introducing divine causation if we hadn't already got independent evidence for the divine' (p. 44), Langford nevertheless maintains that unthought possibilities' should not be ruled out in the manner of a prejudiced theorist' (p. 45). He thinks that such possibilities are left open in his concept of miracle, which makes the prior assumption that independent grounds for belief in God' exist (p. 51) before affirming that, given that God exists, miracles may be consistently and substantively understood in terms of a special distinguishable (pp. 50, 51) sort of inter-psychosomatic influence. He concedes, of course that his concept would rule out those miracles that appear to be quite apart from the working of grace through human minds' (p. 51). I think, however, that Langford's thesis is faulty at key places.